1975
DOI: 10.1111/j.1476-5381.1975.tb07426.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins in Pyometrial Fluid From the Cow, Bitch and Ferret

Abstract: Pyometra is a disorder of the uterus usually associated with bacterial infection plus obstruction. Large quantities of fluid often collect in the uterus during this condition. Pyometrial fluid obtained from three species was found to contain prostaglandin F2α, usually in large quantities. Prostaglandin E2 was present in smaller quantities in five of the six samples. These findings are discussed in relation to the known occurrence of prostaglandins in inflammatory fluid, and to the problem of infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In pyometra, bacterial infection and subsequent endotoxin release cause the endometrium to produce prostaglandins which is reflected by an increase in PGFM concentrations (Heap and Poyser ; Vandeplassche et al. ; Hagman ; Hagman et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In pyometra, bacterial infection and subsequent endotoxin release cause the endometrium to produce prostaglandins which is reflected by an increase in PGFM concentrations (Heap and Poyser ; Vandeplassche et al. ; Hagman ; Hagman et al.…”
Section: Discussionmentioning
confidence: 99%
“…In pyometra, bacterial infection and subsequent endotoxin release cause the endometrium to produce prostaglandins which is reflected by an increase in PGFM concentrations (Heap and Poyser 1975;Vandeplassche et al 1991;Hagman 2004;Hagman et al (2006a,b)). Hagman et al (2006a,b) found significantly higher mean serum PGFM concentrations in dogs with pyometra (6278 pmol/l) compared to CEH/ mucometra (415 pmol/l) and control (86 pmol/l) dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study has shown prematurely elevated concentrations of PGFM in plasma which have been associated with luteolysis in two mares with endometritis (Neely et a1 1979) and it was hypothesised that uterine infection led to increased synthesis of PGFZq by the inflammatory process and/or the presence of bacterial toxins. Pyometrial fluid from bitches, cows and ferrets has been shown to contain high concentrations of PGF, and PGE (Heap and Poyser 1975) and in cattle the concentrations of PGF in pyometrial fluid were significantly correlated with plasma concentrations of PGFM (Nkuuhe 1 982).…”
Section: Mean K Semmentioning
confidence: 99%
“…In women, uterine inflammation associated with an infectious process may lead to a diminution of RI values of uterine arteries [12]. Furthermore, a previous study in bitches with pyometra reported an increase in the intrauterine concentration of prostaglandin E, which may also lead to an increase in uterine perfusion [25,26]. In addition to prostaglandins, nitric oxide, a potent vasodilator, is also released locally in several mammalian species during endometrial inflammation [27,28].…”
Section: Discussionmentioning
confidence: 99%